Pengembangan Perikanan Tangkap dan Hasil Olahannya di Pesisir Kabupaten Bone Bolango Gorontalo - Frahmawati Bumulo; Meyko Panigoro (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2021)
The purpose of this research is, how to develop capture fisheries and their processed products on the coast of Bone Bolango, Gorontalo Province. The analytical methode used in this research is SWOT analysis. The SWOT analysis methode is used to analysis capture fisheries development strategies in Bone Bolango Gorontalo Province. The results showed that from the results of the SWOT analysis, a capture fisheries development strategy and its processed products in increasing Regional Original Income were described in several aspects, a) Improving facilities and infrastructure for coastal area development, b) Disseminating information about coastal and marine resources through local media an national, c) Developing appropriate models and technologies and environmentally friendly use of marine resources, d) Supporting groups of fishermen the production of processed capture fishery products, f) Incresing the capacity of fishing communities regarding the utilization and management of capture fisheries resources,